Quo Vadis Botulinum Toxin: Normative Constraints and Quality of Life for Patients With Idiopathic OAB? - Mühlstädt, Sandra; Mischner, Shahidul; Kranz, Jennifer; Anheuser, Petra; Mohammed, Nasreldin; Steffens, Joachim A.; Fornara, Paolo (Frontiers in Surgery, 2018)
Background: Idiopathic overactive bladder (iOAB), with or without urge incontinence (UI), has significant psychosocial effects on patients’ quality of life (QoL). The first choice of treatment for iOAB is anticholinergics and, alternatively, the β-3-adrenoceptor agonist mirabegron. However, systemic side effects and contraindications should be considered for both medications. Objective: We report the efficacy, safety and effects on QoL of botulinum toxin therapy (onabotulinum toxin type A, BOTOX®, Allergan) among patients with iOAB +/- UI. Patients and Methods: Between 2005 and 2013, 51 patients were treated with onabotulinum toxin A (100 units). The inclusion criteria were the presence of confirmed iOAB +/- UI with previous use of anticholinergic medication. Micturition frequency, pad count, postvoid residual volume and QoL were evaluated using two validated questionnaires (the Client Satisfaction Questionnaire-8 (CSQ-8) and the King’s Health Questionnaire (KHQ)). Statistical analysis was performed with SPSS 24.0 (p<0.05). Results: After botulinum toxin injection, a significant improvement in iOAB +/- UI symptoms was observed. The micturition frequency decreased from 10.4±0.5 to 5.2±0.4 micturitions per day (p = 0.026), and the pad count decreased from 3.6±1.0 to 1.2±0.3 pads per day (p = 0.033). Anticholinergics were not used during the administration of botulinum toxin therapy. Complications and postoperative need for intermittent self-catheterization (ISC) were not observed. Overall, 72% and 24% of patients reported being "satisfied" or "very satisfied" with the treatment. Additionally, 66% of patients would choose botulinum toxin again for the treatment of iOAB. Conclusion: Botulinum toxin therapy is an efficient, safe, and life-improving treatment for iOAB.